1999
DOI: 10.1002/(sici)1099-0909(199909)5:3<155::aid-dys143>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental dyslexia: The role of the cerebellum

Abstract: Children with dyslexia suffer from unexpected problems in reading, writing and spelling.  The dominant causal hypothesis has been that the deficits arise from some impairment in phonological processing ability.  Initial studies revealed that children with dyslexia suffered severe deficits in skills including not only phonological skill but also picture naming speed, bead threading and balance.  Given the growing evidence that the cerebellum is directly involved in acquiring ‘language dexterity’, all the above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(26 citation statements)
references
References 74 publications
2
18
0
6
Order By: Relevance
“…Frank and Levinson [7] were the first to report subjectively that dyslexic children showed neurological signs of cerebellar-vestibular deficiency (i.e., positive Romberg test, difficulty in tandem walking, articulatory speech disorders, hypotonia, and several dysmetric deficits). The cerebellar deficit hypothesis was confirmed by Nicolson and Fawcett [8] showing deficit in balance and motor coordination in a population of dyslexic children; their postural stability was affected by a secondary task, shifting attention away from the primary postural one. These authors suggested that dyslexics need to invest more attentional resources than non-dyslexics to control their balance when two tasks are performed simultaneously.…”
Section: Introductionmentioning
confidence: 82%
“…Frank and Levinson [7] were the first to report subjectively that dyslexic children showed neurological signs of cerebellar-vestibular deficiency (i.e., positive Romberg test, difficulty in tandem walking, articulatory speech disorders, hypotonia, and several dysmetric deficits). The cerebellar deficit hypothesis was confirmed by Nicolson and Fawcett [8] showing deficit in balance and motor coordination in a population of dyslexic children; their postural stability was affected by a secondary task, shifting attention away from the primary postural one. These authors suggested that dyslexics need to invest more attentional resources than non-dyslexics to control their balance when two tasks are performed simultaneously.…”
Section: Introductionmentioning
confidence: 82%
“…Yet, along with these skills, cognitive learning mechanisms not specifically related to linguistic processing appear to mediate reading acquisition (Hulme, Goetz, Gooch, Adams, & Snowling, 2007; Windfuhr & Snowling, 2001). Specifically, non-linguistic mechanisms of associative learning may explain how reading is learned both implicitly and explicitly (Nicolson & Fawcett, 1999). Establishing the connections between written (grapheme) and spoken (phoneme) units is in fact the core learning activity of reading acquisition (Richardson & Lyytinen, 2014).…”
mentioning
confidence: 99%
“…One aetiological theory of dyslexia proposes that many of the behavioural symptoms stem from a common deficit in the development and functioning of the cerebellum. According to this theory, impairments of the cerebellum cause deficits in motor control such as posture and balance, and additional difficulties in achieving ‘automaticity’ of other learned skills, including those that impact directly upon literacy (e.g., grapheme to phoneme conversion and handwriting proficiency) (Nicolson & Fawcett, 1990, 1999). Supporting evidence for cerebellar abnormalities in dyslexia has been demonstrated in neuroimaging studies for measures of brain biochemistry (Rae et al., 1998), neural morphology (Rae et al., 2002) and functional activity related to motor learning (Nicolson et al., 1999).…”
mentioning
confidence: 99%
“…Several screening batteries for dyslexia, such as the Pre‐school Early Screening Test (PREST; Fawcett et al., 2001a) and the Dyslexia Screening Test – Junior (Fawcett & Nicolson, 2004) obtain measures of cerebellar function, including postural stability. The cerebellar deficit hypothesis predicts that balance in dyslexia is threatened by the failure to automate postural responses to perturbation, creating a continuous requirement for attentional resources to be drawn away from current activity toward the monitoring of posture (Nicolson & Fawcett, 1999). Balance in individuals with dyslexia is therefore predicted to depend upon a ‘conscious compensation’ process (Nicolson & Fawcett, 1999, p. 171) rather than on automatic control.…”
mentioning
confidence: 99%
See 1 more Smart Citation